International management : culture, strategy, and behavior - Luthans, Fred; Doh, Jonathan P. (Boston : McGraw-Hill Irwin, 2009)
'International Management' applies management concepts and techniques to their contexts in firms working in multinational, multicultural environments. This book sets the standard for international management texts with its research-based content and its balance between culture, strategy, and behaviour.
pt. 1. Environmental foundation -- 1. Globalization and international linkages -- 2. The political, legal, and technological environment -- 3. Ethics and social responsibility -- pt. 2. The role of culture -- 4. The meanings and dimensions of culture -- 5. Managing across cultures -- 6. Organizational cultures and diversity -- 7. Cross-cultural communication and negotiation -- pt. 3. International strategic management -- 8. Strategy formulation and implementation -- 9. Entry strategies and organizational structures -- 10. Managing political risk, government relations, and alliances -- 11. Management decision and control -- pt. 4. Organizational behavior and human resource management -- 12. Motivation across cultures -- 13. Leadership across cultures -- 14. Human resource selection and development across cultures -- Skill-building and experiential exercises -- Personal skill-building exercises -- In-class simulations.
colour map on endpaper.
Revised edition of : International management / Richard M. Hodgetts, Fred Luthans, Jonathan Doh. 6th ed. 2006.
Includes bibliographical references : (pages 568-571) and indexes.
Keywords: International business enterprises -- Management; International business enterprises -- Management -- Case studies